Internalization of Islamic Egalitarianism in the Novel Bumi Cinta by Habiburrohman EL Shirazy - Devi Khavita Kharisma; Okky Ambarita Cahya utami (Institut Agama Islam Tarbiyatut Tholabah, 2025)
Equality among Muslims is a must. The equality in question is in the social sphere, and other human relationships as long as it does not involve linking the teachings of tawhid from each belief. Egalitarian awareness or equality is important to be applied to unite various differences in order to create peace and harmony between religious communities in each region. This phenomenon is also depicted in the novel Bumi Cinta by Habiburrohman EL Shirazy. Although the novel tells the story of a santri who can be said to be a person who has a strong stance in his religion, but in his place of residence in Moscow Russia, he can still live well side by side with the surrounding community who are not Muslim. How is the form of Islamic Egalitarianism reflected in the novel Bumi Cinta by Habiburrohman EL Shirazy? 2. What is the impact of the form of Islamic Egalitarianism reflected in the novel Bumi Cinta by Habiburrohman EL Shirazy? This research uses qualitative data analysis techniques. The results of this study indicate that Islamic Egalitarianism reflected in the novel Bumi Cinta by Habiburrohman EL Shirazy is the most effective da’wah strategy to increase the number of followers of Islam. Even the followers of Islam are voluntary and forced. Thus, the awareness of preaching in a peaceful way like this should be applied in real life.